2022
DOI: 10.3389/fimmu.2022.1031746
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating CD8/CD103/TIM-3-expressing lymphocytes in epithelial ovarian cancer co-express CXCL13 and associate with improved survival

Abstract: Reactivation of tumor infiltrating T lymphocytes (TILs) with immune checkpoint inhibitors or co-stimulators has proven to be an effective anti-cancer strategy for a broad range of malignancies. However, epithelial ovarian cancer (EOC) remains largely refractory to current T cell-targeting immunotherapeutics. Therefore, identification of novel immune checkpoint targets and biomarkers with prognostic value for EOC is warranted. Combining multicolor immunofluorescent staining’s with single cell RNA-sequencing ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Furthermore, the inhibition of TNFRSF1B led to a notable modification of the immune microenvironment in an OC mouse model, resulting in suppressed tumor growth. These findings highlight the potential clinical significance of targeting TNFRSF1B for immunotherapy and enhance our understanding of the factors contributing to the limited success observed in OC immunotherapeutic approaches (145). Yakubovich et al reported that cancer cells that migrated into/out of tumors possessed more mesenchymal stromal cells than those that exited and deserted tumors.…”
Section: T Cellsmentioning
confidence: 83%
“…Furthermore, the inhibition of TNFRSF1B led to a notable modification of the immune microenvironment in an OC mouse model, resulting in suppressed tumor growth. These findings highlight the potential clinical significance of targeting TNFRSF1B for immunotherapy and enhance our understanding of the factors contributing to the limited success observed in OC immunotherapeutic approaches (145). Yakubovich et al reported that cancer cells that migrated into/out of tumors possessed more mesenchymal stromal cells than those that exited and deserted tumors.…”
Section: T Cellsmentioning
confidence: 83%